Substitution of Papaya Tree Trunks (Carica Papaya) as Rough Feed on the Quality of FH Cow Milk - Prasetyo, Aris Budi; Purwadi, Purwadi (Universitas Veteran Bangun Nusantara, 2025)
The study aims to determine the effect of papaya tree trunk substitution (Carica papaya) as roughage on the quality of FH cow milk in Boyolali. This study used 16 lactating FH cows with an average body weight of 431.75 + 50.99 kg (CV = 11.82%) and an average milk production per day of 11.12 + 0.96 liters (CV = 8.61%). The average production period of cows is the 2nd lactation period, 2nd to 5th months. The study used a Completely Randomized Design with four treatments and four replications; feed treatments in dry matter were T0: 30% concentrate, 10% tofu dregs, 60% elephant grass, T1: 30% concentrate, 10% tofu dregs, 40% elephant grass, 20% papaya stems, T2: 30% concentrate, 10% tofu dregs, 20% elephant grass, 40% papaya stems, T3: 30% concentrate, 10% tofu dregs, 0% elephant grass, 60% papaya stems. Parameters of milk quality aspects include milk specific gravity, protein content, fat content, lactose, solid non-fat and total solid. This study showed differences in fat content and total solids between T0, T1, T2 and T3, but there was no treatment effect on milk production, Specific gravity, protein content, lactose and SNF milk. This study concludes that using papaya tree trunks as a substitute for fresh greens can maintain the milk productivity of FH cows. Giving 40% papaya tree trunks combined with 20% elephant grass as a roughage produces the same milk production as providing 60% elephant grass.